2010
DOI: 10.1007/s00018-010-0458-8
|View full text |Cite
|
Sign up to set email alerts
|

An ancient cytokine, astakine, mediates circadian regulation of invertebrate hematopoiesis

Abstract: Invertebrate circulating hemocytes are key players in the innate immune defense and their continuous renewal from hematopoietic tissues is tightly regulated in crustaceans by astakine, a new family of cytokines sharing a prokineticin (PROK) domain. In vertebrates, brain PROKs function as transmitters of circadian rhythms and we present evidence that hemocyte release from hematopoietic tissues in crayfish is under circadian regulation, a direct result of rhythmic expression of astakine. We demonstrate that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 26 publications
2
24
1
Order By: Relevance
“…Aeromonas hydrophila used in the present study were originally isolated from water of artificial lake within Qingdao Agricultural University and cultured in LuriaeBertani's rich nutrient medium supplemented with 100 mg L À1 ampicillin overnight at 28 C. Subsequently, bacteria were washed three times with CFS (Crayfish Saline Buffer, 0.2 M NaCl, 5.4 mM KCl, 10 mM CaCl 2 , 2 mM NaHCO 3 , pH 6.8) [22] to remove the culture medium and dissolved in CFS. Bacterial concentration was measured with viable plate counts and recorded by colony forming units (CFUs) per milliliter.…”
Section: Experimental Animals and Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Aeromonas hydrophila used in the present study were originally isolated from water of artificial lake within Qingdao Agricultural University and cultured in LuriaeBertani's rich nutrient medium supplemented with 100 mg L À1 ampicillin overnight at 28 C. Subsequently, bacteria were washed three times with CFS (Crayfish Saline Buffer, 0.2 M NaCl, 5.4 mM KCl, 10 mM CaCl 2 , 2 mM NaHCO 3 , pH 6.8) [22] to remove the culture medium and dissolved in CFS. Bacterial concentration was measured with viable plate counts and recorded by colony forming units (CFUs) per milliliter.…”
Section: Experimental Animals and Bacteriamentioning
confidence: 99%
“…To measure total hemocyte count (THC) in hemolymph of crayfish, hemolymph was sampled at different time points after treatment with 24 C/18 C 12 h/12 h temperature cycles, and fixed with 10% formalin in CFS according to Watthanasurorot et al [22]. Hemolymph was dropped onto a clean hemocytometer and THC was examined under phase-contrast microscope.…”
Section: Total Hemocyte Countmentioning
confidence: 99%
“…Recently, it was found that Astakines play essential roles in the hematopoiesis of invertebrates [68,69].…”
Section: Novel Types Of Venom Peptides With Five Disulfide Bridgesmentioning
confidence: 99%
“…38 Ast1 is highly expressed in the early morning after a dark period, and expression gradually decreases during exposure to light. Recent genetic and physiologic evidence has shown that vertebrate PROKs are transmitters of circadian rhythms of the suprachiasmatic nucleus in the brain of mammals.…”
Section: Crustacean Hematopoiesis Is Rhythmically Controlledmentioning
confidence: 99%